Celiac Plexus Denudation in Triangle Dissection in Pancreatico Duodenectomy: Perioperative Anesthetic Implications (Kathmandu University Medical Journal, 2022)
This is a case report of inadvertent right celiac plexus denudation during triangle dissection during the surgery for carcinoma of pancreas under combined general epidural anaesthesia. Operative removal of the ganglia has its own autonomic effects, which are important to observe for anesthesiologists and perioperative critical care physicians alike.